STRATEGI BERTAHAN HIDUP SUPIR ANGKOT DI KOTA PEKANBARU - Eka Cendani Pangaribuan; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Angkot is one of the public transportation in Pekanbaru are now starting deserted passenger. The fewer passangers caused the difficult angkot driver to full fill their needs. The purpose of this reserch is to know how is the angkot driver’s strategies to fullfill their needs with decrease income and what cause they survive as a angkot driver in Senapelan-Tangkerang route Pekanbaru . The data research is collected through interviews, obeservation and data analysis document with kualitatife descriptive. The vesult of this reseach can be concluded that the angkot drivers used theree strategies in their life. The three strategies are active strategy, passive strategy and network strategy. To be able hs famill in order to survive . The main factor that make angkot driver survive is caused there is not ability in other fields, lack of work experiences, unacceptable education for themselves, and comfort permanent job as angkot drivers.Keywords: Angkot, Driver, Survival Strategy